Epidemiology of major depressive disorder in South Africa (1997–2015): a systematic review protocol - Nglazi, Mweete D (BMJ Open, 2016)
INTRODUCTION: Major depressive disorder (MDD) is a leading cause of disease and disability globally and in South Africa. Epidemiological data for MDD are essential to estimate the overall disease burden in a country. The objective of the systematic review is to examine the evidence base for prevalence, incidence, remission, duration, severity, case fatality and excess mortality of MDD in South Africa from 1997 to 2015. METHODS AND ANALYSIS: We will perform electronic searches in PubMed, PsycINFO, Scopus and other bibliographical databases. Articles published between January 1997 and December 2015 will be eligible for inclusion in this review. The primary outcomes will be prevalence, incidence, remission, duration, severity, case fatality and excess mortality of MDD. The secondary outcomes will be risk factors and selected populations for MDD. If appropriate, a meta-analysis will be performed. If a meta-analysis is not possible, the review findings will be presented narratively and in tables. Subgroup analyses will be conducted with subgroups defined by population group, rural/urban settings and study designs, if sufficient data are available. ETHICS AND DISSEMINATION: The systematic review will use published data that are not linked to individuals. The review findings may have implications for future research prioritisation and disease modelling of MDD to estimate its morbidity burden in South Africa, and will be disseminated electronically and in print through peer-reviewed publications. TRIAL REGISTRATION NUMBER: International Prospective Register of Systematic Reviews (PROSPERO) CRD42015024885.